2019
DOI: 10.9734/ajrid/2019/v2i130092
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Anti-microbial Drug Resistance in Childhood Typhoid Fever in a Selected Hospital in Karachi, Pakistan

Abstract: Introduction: Typhoid fever is a major public health issue in Pakistan. Variations in clinical manifestations make diagnosis a challenging task. Over use of antibiotics make the organism resistant. Antibiotic resistance is currently the most threatening issue as regards to infection control and our study would be helpful in the understanding of this feature of the microbes. The main purpose of this study was to determine the antimicrobial drug resistance and sensitivity pattern in Salmonella typhi and S. parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…A 2019 study conducted at a private hospital in Karachi found that over two-thirds of patients with a positive blood culture for S. typhi and S. paratyphi yielded multidrug resistant (MDR) isolates [65]. This study confirms previous findings of a high degree of MDR S. typhi and S. paratyphi in Karachi, particularly among children in urban squatter settlements [46,65,66,68].…”
Section: Bacterial Ntd Infections In Karachisupporting
confidence: 79%
See 4 more Smart Citations
“…A 2019 study conducted at a private hospital in Karachi found that over two-thirds of patients with a positive blood culture for S. typhi and S. paratyphi yielded multidrug resistant (MDR) isolates [65]. This study confirms previous findings of a high degree of MDR S. typhi and S. paratyphi in Karachi, particularly among children in urban squatter settlements [46,65,66,68].…”
Section: Bacterial Ntd Infections In Karachisupporting
confidence: 79%
“…Furthermore, antimicrobial drug resistance remains one of the most critical public health challenges faced by Pakistan, resulting in increasingly severe infections and complications, longer hospital stays, and increased mortality rates [67]. In Karachi, the development of antimicrobial drug resistance in Salmonella typhi and Salmonella paratyphi has presented major obstacles in terms of effectively treating typhoid patients, as local physicians often have very limited options for typhoid drug prescription [65,66]. A 2019 study conducted at a private hospital in Karachi found that over two-thirds of patients with a positive blood culture for S. typhi and S. paratyphi yielded multidrug resistant (MDR) isolates [65].…”
Section: Bacterial Ntd Infections In Karachimentioning
confidence: 99%
See 3 more Smart Citations